THE COMPARISON OF POLITE REQUEST STRATEGY USED BY STUDENTS OF BIMA AND SASAK IN MATARAM UNIVERSITY - SUPRIADIN, SUPRIADIN (Universitas Mahasaraswati Mataram, 2019)
This study aims to investigate the use of polite requesting strategy by students of Sasak and Bima in Mataram University. The data were obtained based on a questionnaire of politeness in three socially different situations, the Sasak and Bima people as participants in this study were asked to make requests in the three situations. The situations were classified according to the three politeness systems on the basis of social relationship between speaker and addressee: hierarchy, deference, and solidarity. This study demonstrates that both groups tend to use the query preparatory strategy in making requests. However, due to cultural differences between Sasak and Bima people, the respondents in the two groups behave differently in terms of how they modify the polite strategy and how they use the politeness markers